The Effect of Problem Based Learning on EFL Studentsâ Critical Thinking Skill and Learning Outcome - Bashith, Abdul; Amin, Saiful (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This research aims to examine the effect of Problem Based Learning (PBL) model to studentsâ critical thinking skill and learning outcome. It was conducted on the 11th graders of social science program at SMAN 6 Malang. The research material was the problems of demography. Research method was quasi experiment with non equivalent control group design. The data analysis used t-test technique. The research result showed that PBL learning model affected studentsâ critical thinking skill and learning outcome in SMAN 6 Malang. The average gain score of experimental class is 33.10, higher than control class, which is 16.24. The result of t-test analysis is 0.000 smaller than the significance of 0.05. It is suggested that PBL becomes one of aalternative teaching models that could be implemented to enhance students critical thingking skill.